The use and value of wild harvested provisioning ecosystem services along a landscape heterogeneity gradient in rural South Africa. Issue 1 (31st December 2022) - Herd-Hoare, S.; Shackleton, C. M.
ABSTRACT: Provisioning ecosystem services (PES) are typically crucial to rural livelihoods, especially in developing countries. However, the links between PES and local biodiversity or landscape heterogeneity are poorly explored. Here, we examined the extent of use and value of locally harvested wild, terrestrial and marine PES (such as wild foods, traditional medicines, firewood, building materials and others) in three villages (35–40 households per village) along a gradient of decreasing landscape heterogeneity. Households at the site with the highest landscape heterogeneity used a greater array of PES (9 ± 4) compared to the intermediate (5 ± 3) and least heterogenous (0.9 ± 0.8) sites. This resulted in a significantly greater annual value of PES to local livelihoods at the most diverse site (US2 656 ± 2 587 per household), compared to US1 120 ± 1 313 at the intermediate site and only US105 ± 193 at the least heterogeneous site. This study shows the importance of access to a diversity of landscapes and PES to support rural livelihoods, which is frequently overlooked in PES valuation studies and in situations of land use change where landscape heterogeneity may decline.